Lifestyle factors associated with sleep quality among filipino young adults - Arante, Mavreen Leigh C.; Cansino, Annika Laura A.; Dollete, Bea Therese P.; Herrera, Lei Dianne A.; Macapobre, Samantha R.; Padayao, Christine S.; Pingco, Francine Ayana C.; Santos, Noriel Joy T. (Manila College of Nursing University of the Philippines Manila, 2016)
Introduction
Sleepiness and sleeplessness are threatening to health and safety (Canadian Sleep Society, 2015). The age group of 18 to 35 years old considers sleep as an elective task wherein other responsibilities are prioritized (APA, 2015). This study aimed to determine the relationship between sleep quality and lifestyle factors such as caffeine consumption, cigarette smoking, alcohol drinking, electronic device use, and physical activity among Filipino young adults.

Methodology
This study utilized a survey research design. Convenience sampling was utilized to gather data from Filipino young adults aged 18-35 years old who are currently living in the Philippines. Web based survey was implemented, containing demographic questions, questions from the PSQI tool, modified version of Caffeine Intake Recall and questions about the participants’ demographic profile, physical activity, smoking, electronic device usage and alcohol consumption. Multiple Linear regression was used to analyze the relationship between sleep quality and its domains with the lifestyle factors — caffeine consumption, cigarette smoking, alcohol drinking, electronic device use, and physical activity.

Results
The study had a total of four hundred and four respondents who participated. Results showed that majority (71%, n=404) have poor overall quality of sleep. Caffeine, smoking, electronic device use were found to be significant predictors of overall sleep quality correlation coefficient of 0.000609, 0.9947373, and 0.0367218, respectively; p value of 0.032, 0.029, and 0.007, respectively significant at 0.05). Consistently, caffeine and alcohol use were found to be significant predictors of some domains of sleep. They were both significant predictors of day time dysfunction (correlation coefficient of 0.0000609 and 0.0314273, respectively; with p value of 0.021 and 0.029, respectively significant at .05). Electronic device usage from 6pm-6am was found to be significant predictor of sleep duration and subjective sleep quality (correlation coefficient 0.0363461 and 0.0192164 respectively; with p value 0.031 and 0.034, respectively significant at .05).

Conclusion and Recommendation
Majority of the sample population of Filipino Young Adults have poor sleep quality. Lifestyle factors such as caffeine consumption, cigarette smoking and electronic device use from 6PM to 6AM are positive predictors of poor sleep quality. The researchers recommend nationwide information drive on risks and dangers of poor sleep quality among the Filipino young adults. For future researches, increasing the sample size and using probability sampling method will enhance representativeness of the target population.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based and N121.2: Intensive Nursing Experience, Community-based) -- University of the Philippines Manila, June 2016.
Keywords: Intensive nursing experience -- Hospital-based.